(untitled) (Research, Society and Development, 2021)
Alley cropping systems and the use of organic fertilizers are considered good practices for the development of sustainable agriculture. The objective of this study was to evaluate the effects of the application of bovine manure and the use of an alley system with Gliricídia sepium plants on the growth and production of jiló in the Roraima savannas, Brazil. The field experiment was arranged in random blocks in a 2 × 5 factorial scheme, with three repetitions. The first factor was the cultivation system (with and without alleys) CA and SA respectively, and the second factor corresponded to the levels of organic matter (MOS) added to the soil (1.21; 2.21; 3.21; 4, 21, and 5.21%). At 30, 60, and 90 days after transplantation, plant height (AP), stem diameter (DT), and number of leaves (NH) were evaluated. Fruits were collected weekly, recording the average mass of fruits (MF), number of fruits per plant (NFP), and yield (RN). The plants of the CA had less development compared to those of the SA. The increase in MOS positively influenced the development and production of the jiló. The use of bovine manure provides an increase in production components. The 5.21% increase in MOS in the system without alleys, provided the best results in DT, NH, MF, NFP, and RN. The cultivation with alleys does not provide an improvement in the jiló production indices.